Influence of weather parameters on purple blotch of onion - and SUDHEER KUMAR, V.K. RAZDAN*, EFATH SHAHNAZ (Indian Phytopathology, 2008)
Seven onion varieties were’ selected to study purple blotch disease progress under field conditions. Disease showed a progressive increase and maximum terminal severity in the 18th standard week (SW). Maximum disease severity (74.05%) was observed in the variety Royal Select and minimum in Pankaj (44.04%). Disease infection rate (r) remained high at the initial stage but declined progressively due to adverse weather conditions and lack of tissue availability. All the varieties tested behaved more or less in same manner. The area under disease progress curve (AUDPC) pointed towards the disease pressure being more in 2004 than in 2003, and Pusa red being less susceptible than other varieties tested. Multiple regression equation was drawn for the disease prediction based on data collected during the year 2003 and 2004 for all the seven cultivars by taking the overall average of the disease severity. In the year 2003, two weather parameters viz. maximum temperature and maximum relative humidity explained 95% variability, whereas, in 2004, rainfall, minimum temperature and maximum relative humidity contributed in disease prediction with 97% precession. In all the varieties, the predicted values lied in close proximity to the observed disease severity.